The impact of wartime conflict on the mental health problems of women in the conflict-hit population in Woldia, Ethiopia - Negussie Deyessa; Kehali Getahun; Ruth Filimona; Abraraw Tadesse (PLoS ONE, 2025)
Background Common mental health problems are of significant public health importance, with severe social and economic impacts that adversely affect individuals’ quality of life. The burden of these problems may worsen during wartime. This study aims to assess the prevalence of war-related common mental health problems, including depression, anxiety disorder, phobia, and posttraumatic stress disorder (PTSD), among women in the Woldia district, Amhara, Ethiopia. Methods A community-based cross-sectional survey was conducted from February to March 2023, involving 1,505 eligible women selected from five kebeles using cluster followed by systematic sampling. The study used the Patient Health Questionnaire-9, Generalized Anxiety Disorder scale, and PTSD Checklist-5 to assess common mental health disorders. In addition to descriptive analysis, the study employed binary and multivariable analysis to evaluate sociodemographic correlates and the presence of comorbidity for each mental disorder. Result Almost half of the women exhibited symptoms of common mental health problems, with about 33% experiencing comorbidity of two or more disorders. Depressive symptoms were more prevalent among older, single women and those with spouses using khat, whereas higher wealth and strong social support were protective factors. Similar risk and protective patterns were observed for generalized anxiety disorder (GAD) and posttraumatic stress disorder (PTSD). Older age, single status, and moderate-income increased risk, while a higher wealth index and stronger social support provided some protection. Conclusion The findings from Woldia reveal a severe mental health crisis among women post-conflict, with elevated levels of depression, anxiety, and PTSD far exceeding global averages. This crisis jeopardizes the well-being of women and has far-reaching implications for families and communities, necessitating an urgent and multi-dimensional approach to address risk and protective factors identified in the study.